Developing successful global strategies for marketing luxury brands - Mosca, Fabrizio; Casalegno, Cecilia, 1979-; Gallo-Martinez, Rosalia, 1964- (Advances in marketing, customer relationship management, and e-services (AMCRMES) book series., 2021)
"This book presents the most relevant upgraded theoretical frameworks and empirical research about the marketing of luxury goods, offering contributions focused on contemporary issues affecting luxury industries such as digital transformation, sustainable development, changes in luxury consumers' behavior, integration between physical and online channels, and the development of social media marketing strategies"--